Influence of Persuasive Communication, Discounts, and Consumer Trust on Shopee Live Purchases at Sivali Factory - Yuliastuti, Handini; Mutiasari, Annisa Indah; Cahyani, Rusnandari Retno (The Graduate School of Sahid University, 2024)
Translator Translator Translator This study examines the impact of persuasive communication, discounts, and consumer trust on purchasing decisions during live-streaming sessions on Shopee, specifically focusing on the Sivali Factory account. The research employs a descriptive quantitative method, using questionnaires distributed to respondents who purchased products from Sivali Factory via Shopee live streaming. The data were analysed using multiple linear regression with SPSS version 25. Findings reveal that discounts and consumer trust significantly influence purchasing decisions, while persuasive communication does not have a significant effect. The study concludes that effective discount strategies and fostering consumer trust are crucial for enhancing purchasing decisions during live-streaming sessions. It is recommended that e-commerce businesses prioritise these factors to boost sales and consumer engagement.